Playing in the Dark with Ali: Portraiture, Race, and Remembrance in Karol Radziszewski's Painting of August Agboola Browne. (2nd January 2021) - Boston, Nicholas
ABSTRACT: August Agboola Browne (1895 – 1976) was a Nigerian-born jazz musician who resided in Poland from 1922 to 1956. Since the discovery and initial publicisation in 2010 of archived documents Browne submitted in 1949 for membership in a veterans' association, on which he declared that he had been an insurgent in the Warsaw Uprising of 1944 under the code name 'Ali', he has been heroised rhetorically and memorialised formally by individuals and institutions in Poland across the political-ideological spectrum as 'the only Black participant in the Warsaw Uprising'. The present article explores the cultural, discursive, historical, and representational implications of one such project: a portrait interpreting Ali by the queer artist Karol Radziszewski (b. 1980) in a style influenced by Pablo Picasso's African Period. The article deploys Morrison's literary-critical concept of 'playing in the dark' to engage with this visual art object, analysing, through an optic of racialisation, what it proposes to do as an act of remembrance, an artefact of portraiture, and a discourse on race, particularly Blackness, specifically Black masculinity.